Insight Into the Mechanisms and the Challenges on Stem Cell-Based Therapies for Cerebral Ischemic Stroke - Liu, Huiyong; Reiter, Sydney; Zhou, Xiangyue; Chen, Hanmin; Ou, Yibo; Lenahan, Cameron; He, Yue (Frontiers in Cellular Neuroscience, 2021)
Strokes are the most common types of cerebrovascular disease and remain a major cause of death and disability worldwide. Cerebral ischemic stroke is caused by a reduction in blood flow to the brain. In this disease, two major zones of injury are identified: the lesion core, in which cells rapidly progress toward death, and the ischemic penumbra (surrounding the lesion core), which is defined as hypoperfusion tissue where cells may remain viable and can be repaired. Two methods that are approved by the Food and Drug Administration (FDA) include intravenous thrombolytic therapy and endovascular thrombectomy, however, the narrow therapeutic window poses a limitation, and therefore a low percentage of stroke patients actually receive these treatments. Developments in stem cell therapy have introduced renewed hope to patients with ischemic stroke due to its potential effect for reversing the neurological sequelae. Over the last few decades, animal tests and clinical trials have been used to treat ischemic stroke experimentally with various types of stem cells. However, several technical and ethical challenges must be overcome before stem cells can become a choice for the treatment of stroke. In this review, we summarize the mechanisms, processes, and challenges of using stem cells in stroke treatment. We also discuss new developing trends in this field.